Code of ethics and public morality in Nigeria: a development praxis (2014)
Nigeria today remains rooted in poverty and underdevelopment regardless of huge promises to deliver dividends of democracy to the people and jumpstart development in sustainable manners. Unfortunately, it is possible to trace the disconnections between promises and outcomes to critical governance and development contextualities of code of ethics, public morality and accountability in the country. Thus, this article explored the contours of these contextualities and x-rayed their existences, implications for development and sustainable pathways